2013
DOI: 10.1016/s0254-6272(14)60030-3
|View full text |Cite
|
Sign up to set email alerts
|

Curative effect of warming kidney and fortifying spleen recipe on diarrhea-predominant irritable bowel syndrome

Abstract: Modified Sishen Wan, for warming the kidney and fortifying the spleen, can effectively treat IBS-D and better control its recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…Accordingly, the inhibition of inflammatory response is pivotal in the progression of ALI. Clinical observation found that LGS could depress ALI [15]. Here we showed that LGS not only suppressed LPS-stimulated inflammation in vitro , but also inhibited LPS-induced ALI in vivo .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Accordingly, the inhibition of inflammatory response is pivotal in the progression of ALI. Clinical observation found that LGS could depress ALI [15]. Here we showed that LGS not only suppressed LPS-stimulated inflammation in vitro , but also inhibited LPS-induced ALI in vivo .…”
Section: Discussionsupporting
confidence: 62%
“…It has been widely used for centuries to clear heat and fire in traditional Chinese medicine. Nowadays, LGS exhibits curative effects on ALI, pharyngitis, amygdalitis and pneumonia [14, 15]. In previous studies, we found that LGS could significantly inhibit the inflammation in LPS-induced ALI rats through suppressing the rise of wet-to-dry ratio of lung tissue and lung permeability.…”
Section: Introductionmentioning
confidence: 94%
“…The 15 articles, 12 journal papers, 3 dissertations, and 1 conference proceeding contained 1551 subjects (922 in trail group and 629 in control group). Among them 4 studies were conducted in Australia [ 27 ], Korean [ 39 ], Hong Kong [ 18 ] and Chinese Mainland [ 37 ], respectively, and published in English. The remaining [ 28 – 36 , 38 , 40 ] were all completed in China and published in Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies [ 18 , 27 , 28 , 31 , 33 – 35 , 38 – 40 ] used random number tables or lists, 1 study [ 29 , 30 ] used draw by lots, while the remaining 3 did not mention the specific methods. We tried to contact the authors and they confirmed that 2 studies [ 36 , 37 ] used random number tables, but the others [ 32 ] did not respond. All the studies used sealed envelopes except 2 [ 29 , 32 ] which had no details about the blending method and did not respond to our emails.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation